Tkanina wzorzysta i inne tkaniny lniane z wczesnośredniowiecznego skarbu monet z Wielkopolski - Antosik, Łukasz; Bogucki, Mateusz; Maik, Jerzy (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2025)
Around 2010-2012, a hoard dating from around 1025-1030 was discovered ‘west of Poznań’, perhaps near Grodzisk Wielkopolski. It contained silver coins and ornaments, probably wrapped in cloth and hidden in a pot. This is secondary information from intermediaries who obtained information about the hoard (which consisted of several hundred coins) from various sources. At least 152 specimens were recorded. The pot also contained 17 fragments of linen fabric in good condition, and several dozen small, damaged remnants. Three different types of products were distinguished. Two fabrics (15 fragments) are plain woven, and one (2 fragments) is patterned. The pattern was obtained by three- or five-thread interlacing of the warp or weft against a plain background. Both canvas fabrics are typical of medieval weaving, and the patterned fabric is an absolute revelation for which no analogies have yet been found. The fabrics preserved in the hoard are the remains of at least three wraps or bags in which their contents were stored in accordance with the owner’s intentions.